Wzornictwo przemysłowe jako kompetencyjna przewaga w budowaniu konkurencyjności przedsiębiorstw - Żyra, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
In a modern innovation and research-based economy, industrial design developments require public support for cooperation between private firms in innovation activities. This article presents a survey of literature and results of author’s studies based on the 2006-2015 period as provided by the System of Strategy Development and on the secondary data from the „Assessment of Design in Poland” survey conducted for PARP in 2014/2015, as a part of evaluation of demand for industrial design. The author attempts to assess the effectiveness of industrial design in Poland as an instrumental tool in the build-up of firm-specific and regional competitive advantages.
Keywords: industrial design; design projects; innovations; creativity; clusters; competitiveness